2006
DOI: 10.1111/j.1365-2222.2006.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glutathione S‐transferase from dust mite, Der p 8 and its immunoglobulin E cross‐reactivity with cockroach glutathione S‐transferase

Abstract: A high frequency of sensitization to mite GST among allergic subjects was observed but the titres of IgE reactivity were low. The IgE cross-reactivity between mite and cockroach GST suggests that GST is a panallergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…For example, tropomyosin, a group-10 allergen, is a well-known pan-allergen that causes cross-reactivity among mites, a variety of invertebrates (5,6) including shrimps and crabs, and parasites, including Anisakis nematodes and roundworms (7)(8)(9). Group-8 mite allergens (glutathione S-transferase) have also been shown to be cross-reactive with other arthropod allergens (10,11). The group-2 allergens are cross-reactive among mite species (12,13) and are the primary allergens responsible for the cross-reactivity between HDM and SM in Korea (14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, tropomyosin, a group-10 allergen, is a well-known pan-allergen that causes cross-reactivity among mites, a variety of invertebrates (5,6) including shrimps and crabs, and parasites, including Anisakis nematodes and roundworms (7)(8)(9). Group-8 mite allergens (glutathione S-transferase) have also been shown to be cross-reactive with other arthropod allergens (10,11). The group-2 allergens are cross-reactive among mite species (12,13) and are the primary allergens responsible for the cross-reactivity between HDM and SM in Korea (14).…”
Section: Introductionmentioning
confidence: 99%
“…[116][117][118][119][120][121][122][123][124][125][126][127][128] We have demonstrated that helminth infection can be associated with increased IgE responses to many different allergens, especially those structurally related to parasite antigens. 116 Individuals infected with filarial parasites were shown to have higher levels of IgE against HDM and cockroach extracts (that have several major allergens with homologues in filarial parasites) but not against timothy grass extract, an allergen extract with just a few minor allergen homologues in helminths.…”
Section: -89mentioning
confidence: 99%
“…118 Similarly, IgE binding to several Ascaris allergens can also be inhibited by Dermatophagoides pteronyssinus (Der p) or Blomia tropicalis (Blo t) extracts, including glutathione-S-transferase (GST). 120 GSTs are major allergens of HDM, 119 cockroach, 135 mold, 136,137 and parasites. 138,139 Among the 13 classes of canonical GSTs, there are many that show very little amino acid conservation.…”
Section: -89mentioning
confidence: 99%
“…These allergens have been found at a high frequency among allergic subjects, but their titers of IgE reactivity were low (9). The mite GST has been demonstrated to be a cross-reactive allergen in D. pteronyssinus and cockroach GST, which suggests that it is a panallergen (9). GST has also been shown as an allergen in Blatella germanica (Bla g 5), arthropods, and fungi (10,11,12).…”
mentioning
confidence: 99%
“…Native and recombinant GSTs have been purified from D. pteronyssinus and are known as Der p 8. These allergens have been found at a high frequency among allergic subjects, but their titers of IgE reactivity were low (9). The mite GST has been demonstrated to be a cross-reactive allergen in D. pteronyssinus and cockroach GST, which suggests that it is a panallergen (9).…”
mentioning
confidence: 99%